Design, synthesis, molecular docking and biological evaluation of thiophen-2-iminothiazolidine derivatives for use against Trypanosoma cruzi. Issue 18 (15th September 2016) - Silva-Júnior, E.F.; Silva, E.P.S.; França, P.H.B.; Silva, J.P.N.; Barreto, E.O.; Silva, E.B.; Ferreira, R.S.; Gatto, C.C.; Moreira, D.R.M.; Siqueira-Neto, J.L.; Mendonça-Júnior, F.J.B.; Lima, M.C.A.; et al.
Graphical abstract: Abstract: In this study, we designed and synthesized a series of thiophen-2-iminothiazolidine derivatives from thiophen-2-thioureic with good anti- Trypanosoma cruzi activity. Several of the final compounds displayed remarkable trypanocidal activity. The ability of the new compounds to inhibit the activity of the enzyme cruzain, the major cysteine protease of T. cruzi, was also explored. The compounds3b, 4b, 8b and8c were the most active derivatives against amastigote form, with significant IC50 values between 9.7 and 6.03 μM. The8c derivative showed the highest potency against cruzain (IC50  = 2.4 μM). Molecular docking study showed that this compound can interact with subsites S1 and S2 simultaneously, and the negative values for the theoretical energy binding ( E b  = −7.39 kcal·mol −1 ) indicates interaction (via dipole–dipole) between the hybridized sulfur sp 3 atom at the thiazolidine ring and Gly66. Finally, the results suggest that the thiophen-2-iminothiazolidines synthesized are important lead compounds for the continuing battle against Chagas disease.